2020
DOI: 10.1155/2020/8820713
|View full text |Cite
|
Sign up to set email alerts
|

First Case of COVID-19-Associated Collapsing Glomerulopathy in Sub-Saharan Africa

Abstract: Although the lungs remain the main target of SARS-CoV-2, other organs, such as kidneys, can be affected, which has a negative impact on the outcomes of COVID-19 patients. Although previous studies of kidney disease in COVID-19 reported mainly SARS-CoV-2-induced tubular and interstitial injury, there is growing evidence coming out of Africa of glomerular involvement, especially collapsing glomerulopathy seen particularly in people of African descent. We report a case of collapsing glomerulopathy revealed by acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…Case reports, small case series, and autopsy studies have shown a wide spectrum of kidney manifestations in COVID-19 patients and have improved our understanding of kidney disease in this population. Reported manifestations in native biopsies include acute tubular injury (ATI) 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , myoglobin cast nephropathy 7 , thrombotic microangiopathy (TMA) 9 , 16 , 20 , 25 , 26 , 27 ; acute interstitial nephritis 14 , 28 , non-collapsing focal and segmental glomerulosclerosis (FSGS) 9 , 19 , 20 , 29 , collapsing glomerulopathy (also known as COVID-19 associated nephropathy, COVAN) 7 , 8 , 9 , 15 , 20 , 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , membranous nephropathy 8 , 20 , 42 , minimal change disease 48 , 49 , 50 , 48 , 49 , 50 , 48 , …”
Section: Introductionmentioning
confidence: 99%
“…Case reports, small case series, and autopsy studies have shown a wide spectrum of kidney manifestations in COVID-19 patients and have improved our understanding of kidney disease in this population. Reported manifestations in native biopsies include acute tubular injury (ATI) 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , myoglobin cast nephropathy 7 , thrombotic microangiopathy (TMA) 9 , 16 , 20 , 25 , 26 , 27 ; acute interstitial nephritis 14 , 28 , non-collapsing focal and segmental glomerulosclerosis (FSGS) 9 , 19 , 20 , 29 , collapsing glomerulopathy (also known as COVID-19 associated nephropathy, COVAN) 7 , 8 , 9 , 15 , 20 , 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , membranous nephropathy 8 , 20 , 42 , minimal change disease 48 , 49 , 50 , 48 , 49 , 50 , 48 , …”
Section: Introductionmentioning
confidence: 99%
“…Direct viral podocyte invasion is supported by electron microscopy findings of coronavirus particles within the cytoplasm of podocytes in native and post-mortem biopsies. Suggestions of CG secondary to cytokine release from systemic COVID-19 manifestations have been proposed, particularly in those with APOL1 high risk genotype and African-Caribbean ethnicity[ 13 - 22 , 24 - 29 ]. Basic-science studies have shown viral infections stimulating interferon production which in turn encourages APOL1 gene expression[ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biopsy studies of kidneys which suffered from collapsing glomerulonephritis, now being called COVAN, had APOL1 gene [25] Collapsing Glomerulonephritis was not documented in any of the SARS-CoV-2 outbreaks that happened in the European and Chinese population probably because these population lack APOL1 genotype [26]. APOL1 gene is also a risk factor for endstage kidney disease associated with hypertension [27]. Two high risk alleles of the gene was documented in a 65-year-old Afro-American male patient of covid-19 in a study, viz., APOL1 G 1 and APOL1 G 2 .…”
Section: Role Of Apol1 Genementioning
confidence: 99%
“…In podocytes, the gene mediates the activation of viral activity. This dysregulates the functions of the cell organelles causing great damages to the podocytes [27][28][29][30][31][32][33][34][35].…”
Section: Role Of Apol1 Genementioning
confidence: 99%